Antigen-based nano-immunotherapy controls parasite persistence, inflammatory and oxidative stress, and cardiac fibrosis, the hallmarks of chronic chagas cardiomyopathy, in a mouse model of trypanosoma cruzi infection - Lokugamage, Nandadeva (2020)
Chagas cardiomyopathy is caused by Trypanosoma cruzi (Tc). We identified two candidate antigens (TcG2 and TcG4) that elicit antibodies and T cell responses in naturally infected diverse hosts. In this study, we cloned TcG2 and TcG4 in a nanovector and evaluated whether nano-immunotherapy (referred as nano2/4) offers resistance to chronic Chagas disease. For this, C57BL/6 mice were infected with Tc and given nano2/4 at 21 and 42 days post-infection (pi). Non-infected, infected, and infected mice treated with pcDNA3.1 expression plasmid encoding TcG2/TcG4 (referred as p2/4) were used as controls. All mice responded to Tc infection with expansion and functional activation of splenic lymphocytes. Flow cytometry showed that frequency of splenic, poly-functional CD4+ and CD8+ T cells expressing interferon-γ, perforin, and granzyme B were increased by immunotherapy (Tc.nano2/4 > Tc.p2/4) and associated with 88%–99.7% decline in cardiac and skeletal (SK) tissue levels of parasite burden (Tc.nano2/4 > Tc.p2/4) in Chagas mice. Subsequently, Tc.nano2/4 mice exhibited a significant decline in peripheral and tissues levels of oxidative stress (e.g., 4-hydroxynonenal, protein carbonyls) and inflammatory infiltrate that otherwise were pronounced in Chagas mice. Further, nano2/4 therapy was effective in controlling the tissue infiltration of pro-fibrotic macrophages and established a balanced environment controlling the expression of collagens, metalloproteinases, and other markers of cardiomyopathy and improving the expression of Myh7 (encodes β myosin heavy chain) and Gsk3b (encodes glycogen synthase kinase 3) required for maintaining cardiac contractility in Chagas heart. We conclude that nano2/4 enhances the systemic T cell immunity that improves the host’s ability to control chronic parasite persistence and Chagas cardiomyopathy.